Teacher’s Spiritual Competence and Its Implication in Islamic Religious Education Learning in Pidie, Aceh - A. Samad, Sri Astuti; Gade, Syabuddin; Basri, Hasan; Silahuddin, Silahuddin; Ariani, Safrina (Universitas Islam Negeri Mataram, 2023)
Teachers have a great responsibility in education as they help direct spiritual aspects to foster good morals in students. The research examines spiritual competence and its implications for learning Islamic Religious Education in schools in Pidie, Aceh. This research is based on the field studyandapplied the qualitative descriptive-analytic method. The study subjects were five teachers, four principals, and three students at the scchoolsin Pidie. Data was collected using interviews, observations, document studies, and focused group dsicussions. The findings showed that the teachers' spiritual competence came from the sincere nature of the teachers in educatingstudents. Such sincerity became the main factor in motivating the teachers to educate sincerely, earnestly, responsibly, and with discipline so that the learning process and the quality of learning could be better. Islamic religious education teachers' spiritual competence has influenced their teaching performance and helped them complete their duties correctly. This spiritual competence also affects the students' morals and enthusiasm to improve their academic achievements. Hence, students have received proper guidance, advice, and role models from teachers in class and extracurricular activities.